Documentary Credit as a Guarantee in International Business and The position of the Iraqi Law - Akrem, Ali Taha (Sulaimani Journal for Humanities, 2025)
This paper studies (Documentary Credit as a Guarantee in International Business and the Position of the Iraqi Law). This research is an analytical study. The core of this subject is that due to the growth of the world in the field of the International Trade, and the documentary credit is the most widely used banking instrument in facilitating contemporary international trade transactions. Traders are turning to it to solve the distrust of import and export. This research is divided into two chapters: Chapter one deals with the Introduction to the documentary Credit. It includes the definition, advantages, disadvantages of documentary Credit and the types of the Documentary Credit in international trade and explains each of them. Chapter Two deals with the parties and Documents of Documentary Credit in international Business Transaction.